Cyberattacks, cyber threats, and attitudes toward cybersecurity policies. Issue 1 (7th October 2021) - Snider, Keren L G; Shandler, Ryan; Zandani, Shay; Canetti, Daphna
Abstract: Does exposure to cyberattacks influence public support for intrusive cybersecurity policies? How do perceptions of cyber threats mediate this relationship? While past research has demonstrated how exposure to cyberattacks affects political attitudes, the mediating role played by threat perception has been overlooked. This study employs a controlled randomized survey experiment design to test the effect of exposure to lethal and nonlethal cyberattacks on support for different types of cybersecurity policies. One thousand twenty-two Israeli participants are exposed to scripted and simulated television reports of lethal or nonlethal cyberattacks against national infrastructure. Findings suggest that exposure to cyberattacks leads to greater support for stringent cybersecurity regulations, through a mechanism of threat perception. Results also indicate that different types of exposure relate to heightened support for different types of regulatory policies. People exposed to lethal cyberattacks tend to support cybersecurity policies that compel the government to alert citizens about cyberattacks. People who were exposed to nonlethal attacks, on the other hand, tend to support oversight policies at higher levels. More broadly, our research suggests that peoples' willingness to accept government cybersecurity policies that limit personal civil liberties and privacy depends on the type of cyberattacks to which they were exposed and the perceptions associated with such exposure.